Inggris - Nurjaman, Muhamad Izazi; Wardiyah, Mia Lasmi; Al-Rasyid, Camelia Sofwan; Eldiani, Nita; Tamami, Ahmad (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the implementation strategy of mosque-based Islamic financial innovations to improve the welfare of rural communities In Indonesia. The research method used is descriptive qualitative with a library research approach. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, to obtain a systematic and comprehensive understanding. The results indicate that mosque-based Islamic financial innovations have significant potential as instruments for village economic empowerment. Various forms, such as mosque-based Islamic financial institutions (BMT), productive waqf, Islamic cooperatives, and the establishment of mosque-based Islamic Microfinance Institutions (LKMS), have been proven to improve community welfare by strengthening access to financing, creating jobs, and developing micro-enterprises. A key finding of this study is that program sustainability is largely determined by the existence of regular evaluation and monitoring mechanisms, active community participation, and strong regulatory support. Therefore, mosque-based Islamic financial innovations have the potential to become an alternative model for inclusive, equitable, and sharia-compliant village economic development.